PENGARUH METODE EKSPOSITORI PADA PERKULIAHAN TAFSIR TARBAWI TERHADAP PENINGKATAN KECAKAPAN BERPIKIR MAHASISWA PRODI PAI - PS, Alaika M. Bagus Kurnia; Sutikno, Sutikno; Khoirunisa, Amelia; Azzahrah, Ardaniyatus; Assalami, M. Ihlal Fauqi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This research aims to investigate the impact of the application of the expository method in tarbawi tafsir lectures on improving the thinking skills of students of the Islamic Education Study Program (PAI) at the Faculty of Tarbiyah and Keguruan UIN Sunan Ampel Surabaya. The expository method is implemented as a learning approach that focuses on delivering information in a systematic and structured manner, with the hope of strengthening students' understanding and skills in interpreting tarbawi tafsir texts. This study used a quasi-experimental design with a control group and an experimental group. The research participants were 3rd-semester students who were taking the tarbawi tafsir course. The research instruments involved a proficiency test before and after the application of the expository method, as well as a questionnaire to collect data on students' perceptions of the learning method. The results of data analysis showed a significant improvement in the proficiency of students who attended the tarbawi tafsir lecture using the expository method compared to the control group. In addition, students' positive responses to the use of the expository method indicate that this approach contributes positively to students' understanding and skills in interpreting tafsir tarbawi texts. This research makes an important contribution to the development of learning methods at the university level, especially in the context of Islamic religious education. Implications.